2019
DOI: 10.1002/ece3.4906
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation phenology and nest survival: Diagnosing heterogeneous effects through time

Abstract: Birds should select nest sites that minimize predation risk, but understanding the influence of vegetation on nest survival has proven problematic. Specifically, the common practice of measuring vegetation on nest fate date can overestimate its effect on nest survival, simply because vegetation at hatched nests grows for a longer period of time than vegetation at nests that were depredated. Here, we sampled the literature to determine the prevalence of this bias in studies of duck breeding ecology. We then use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
0
15
1
Order By: Relevance
“…In contrast to other recent studies (Gibson et al, ; McConnell et al, ; Ringelman & Skaggs, ; Smith et al, ), we did not find evidence that timing of sampling (projected hatch date vs. failure date) influenced our estimates or inferences regarding the positive association between VOR and nest survival. Most nests were constructed in evergreen shrubs (primarily common juniper, Juniperus communis ); retention of leaves and slow growth of these plants likely prevent appreciable changes in visual obstruction during the incubation period.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to other recent studies (Gibson et al, ; McConnell et al, ; Ringelman & Skaggs, ; Smith et al, ), we did not find evidence that timing of sampling (projected hatch date vs. failure date) influenced our estimates or inferences regarding the positive association between VOR and nest survival. Most nests were constructed in evergreen shrubs (primarily common juniper, Juniperus communis ); retention of leaves and slow growth of these plants likely prevent appreciable changes in visual obstruction during the incubation period.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, researchers' ability to detect the relationship varies among species. As noted by Ringelman and Skaggs (), many studies of duck nest survival measure vegetation when the nest is found because nests are located by flushing the female. This method is appropriate for some taxa (e.g., some waterfowl and songbirds), but not for species where investigator disturbance may induce nest abandonment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations